HUBUNGAN ANTARA PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN ISPA PADA BAYI USIA 6-12 BULAN DI PUSKESMAS PURWOKERTO BARAT - ., Sumarni; Retnowati, Misrina; Rahmayati, Adha Dina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
The lowness of exclussive breastfeeding can influence infection of respiratory tract disease to the baby which is higher happen to the baby given formula milk than Breastmilk. This is explain that baby is growth and defense better with ASI breastfeed. Zinc composition in ASI is needed for the metabolism process inside the body and breastmilk could give protection to the infection of respiratory tract disease. This reseach want to Knowing the relation of exclussive breastfeeding toward the infection of respiratory tract disease happen to the babies age 6-12 months at the local government clinic of Purwokerto Barat in 2013. This research used observational research with case control method and accidental sampling sample. The population of this research is the baby start from age 6-12 months in the local government clinic of west Purwokerto from January until February 2013 with 70 respondent. The research instrument is using observational sheet and Chi Square Analysis. Almost exclussive breastfeeding to the baby age 6-12 months (52,4%) infection of respiratory tract disease happen to the baby and not both are 50%. There is a relation of exclussive breastfeeding toward infection of respiratory tract disease to the baby with precentage p- value < Î± (0.000 < 0,05 ), OR = 0,074 (0,017 to 0,323). There is a relation of exclussive breastfeeding toward the infection of respiratory tract disease happen to the babies Â 6-12 months at the local government clinic of Purwokerto Barat in 2013. The information about some factors that influence infection of respiratory tract disease which is can broader parents knowledge especially mother about the factor of infection of respiratory tract disease and decreasing the number of infection of respiratory tract disease. Keywords : Exclussive breastfeeding, Infection of respiratory tract disease, The baby Â 6-12 months.